IAA17/AXR3: Biochemical insight into an auxin mutant phenotype - Ouellet, François (American Society of Plant Physiologists, 2001)
The Aux/IAA genes are rapidly and specifically induced by the plant hormone auxin. The proteins encoded by this gene family are short-lived nuclear proteins that are capable of homodimerizing and heterodimerizing. Molecular, biochemical, and genetic data suggest that these proteins are involved in auxin signaling. The pleiotropic morphological phenotype and altered auxin responses of the semidominant axr3-1 mutant of Arabidopsis result from a single amino acid change in the conserved domain II of the Aux/IAA protein IAA17. Here, we show that the biochemical effect of this gain-of-function mutation is to increase the half-life of the iaa17/axr3-1 protein by sevenfold. Intragenic mutations that suppress the iaa17/axr3-1 phenotype have been described. The iaa17/axr3-1R3 revertant contains a second site mutation in domain I and the iaa17/axr3-1R2 revertant contains a second site mutation in domain III. Transient expression assays show that the mutant forms of IAA17/AXR3 retain the ability to accumulate in the nucleus. Using the yeast two hybrid system, we show that the iaa17/axr3-1 mutation does not affect homodimerization. However, the iaa17/axr3-1 revertants counteract the increased levels of iaa17/axr3-1 protein by decreasing the capacity of the mutant protein to homodimerize. Interestingly, heterodimerization of the revertant forms of IAA17/AXR3 with IAA3/SHY2, another Aux/IAA protein, and ARF1 or ARF5/MP proteins is affected only by changes in domain III. Collectively, the results provide biochemical evidence that the revertant mutations in the IAA17/AXR3 gene affect the capacity of the encoded protein to dimerize with itself, other members of the Aux/IAA protein family, and members of the ARF protein family. By extension, these findings may provide insight into the effects of analogous mutations in other members of the Aux/IAA gene family.